Communities and cultural heritage : global issues, local values - Higgins, Valerie; Douglas, Diane (London ; New York, NY : Routledge/Taylor & Francis Group, 2020)
"Communities and Cultural Heritage explores the relationship between communities, their cultural heritage, and the global forces that control most of the world's wealth and resources in today's world. Bringing together scholars and heritage practitioners from nine countries, this book contributes to the ongoing dialogue on community heritage, by analysing impediments to full community participation. The undermining of local communities comes at a high price. As the chapters in this book demonstrate, the knowledge embedded within traditional and Indigenous heritage creates communities that are more resilient to environmental and social stressors and more responsive to contemporary challenges such as climate change, environmental degradation, post-disaster recovery and re-location. Cultural heritage practices often fail to capitalise upon local knowledge and traditional skills and undervalue the potential contribution of local communities in finding creative and resourceful solutions to the issues they are confronting. Arguing that the creation of successful community heritage projects requires ongoing reflection on the aims, methods, financing and acceptable outcomes of said projects, the volume also demonstrates that the decolonization of western-focused heritage practices is an ongoing process, by which subaltern groups are brought forward and given a space in the heritage narrative. Reflecting on trends that impact communities and heritage sites across different geographical regions, Communities and Cultural Heritage will be of interest to academics, students and practitioners of cultural heritage, archaeology and anthropology around the world"--
Preface / Valerie Higgins, Diane Douglas & George Smith -- Communities and cultural heritage, global issues, local values : an introduction / Valerie Higgins and Diane Douglas -- Valuing and protecting the past in contemporary society / George S. Smith -- Cultural heritage, empowerment and the social transformation of local communities / Fekri Hassan -- 'Heritage communities' in an age of migration : urban youths' narratives of translocalitional belonging / Kaja Hannedatter Sontum -- Overtourism in historic cities and its impact on the local community. Cities without citizens / Valerie Higgins -- Agricultural heritage systems, their resilience and climate smart communities / Parviz Koohafkan and Thomas L. Price -- Heritage management, community engagement and resilience in Senegal / Ibrahima Thiaw and Mouhamed A. Ly -- Local craft knowledge and heritage-making in the aftermath of a capacity-building project in southern Africa : who are the locals? / Per Ditlef Fredriksen and Foreman Bandama -- Archaeology, communities and economic development : a Pandora's box / K. Anne Pyburn -- Heritage preservation and indigenous communities in the United States : a case for community-based participatory research / Joe Watkins -- Local and global communities as heritage stewards / Arlene K. Fleming -- Realities and requisites in community-based heritage management / Peter G. Gould -- Local engagement in public-private partnerships for heritage management / William H. Jansen -- Tourism and sustainability in the historic city of Rome : challenge or threat? / Barbara Staniscia -- How indigenous knowledge can contribute to mitigating global climate change : seeing the forest and the trees / Diane L. Douglas -- Disaster risk management of cultural heritage through community engagement / Rohit Jigyasu -- Cultural heritage in disasters : people centred responses for building resilience / Aparna Tandon -- Epilogue. Engaging global issues and local values : scales, culture, concepts and politics / Christopher Prescott.
OCLC-licensed vendor bibliographic record.
Keywords: Cultural property -- Protection -- Social aspects; Historic sites -- Management -- Social aspects; Communities -- Historiography; Local history; Community development; Culture and globalization; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Anthropology / Cultural